The Legal Rights and Challenges of COVID-19 Patients Accessing Private Healthcare in Nigeria - Aidonojie, Paul Atagamen; Okuonghae, Nosakhare; Ukhurebor, Kingsley Eghonghon (BESTUUR, 2022)
The COVID-19 pandemic has overwhelmed healthcare providers all over the world. Nigeria has also had its fair share of the health crisis caused by COVID-19. Despite the apparent shortcomings of public healthcare in combating the COVID-19 pandemic, the participation of private healthcare providers in caring for COVID-19 patients in Nigeria has been limited by legal and regulatory constraints. This study employs a hybrid research method. The study found insufficient medical facilities and care for COVID-19 patients in government-owned isolation centers. It was concluded and recommended that there is a need to whittle down the laws and regulations limiting private health providers from caring for COVID-19 patients. Furthermore, there is a need to set some ethics and guidelines for private healthcare providers who intend to care for COVID-19 patients.